2018
DOI: 10.1007/978-3-319-77736-8_4
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Metabolism of Glioblastoma

Abstract: Glioblastoma multiforme (GBM) develops on glial cells and is the most common, as well as the deadliest, form of brain cancer [1]. As in pancreatic cancers, distinct combinations of genetic alterations in GBM subtypes induce a multiplicity of metabolic phenotypes, which explains the variability of GBM sensitivity to current therapies targeting its reprogrammed metabolism. Therefore, it is becoming imperative for cancer researchers to account for the metabolic heterogeneity within this cancer type before making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…The Warburg effect, despite having been conceptualized by Otto von Warburg over 100 years ago, has received renewed interest of late in the search for valid drug targets in solid tumors including diffuse gliomas [41,42,43]. This strategy of chemotherapeutic drug development allows for the avoidance of extremely morbid side effects seen with most other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect, despite having been conceptualized by Otto von Warburg over 100 years ago, has received renewed interest of late in the search for valid drug targets in solid tumors including diffuse gliomas [41,42,43]. This strategy of chemotherapeutic drug development allows for the avoidance of extremely morbid side effects seen with most other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…7 While major metabolic changes in tumors include enhanced aerobic glycolysis, so-called the Warburg effect, and glutamine metabolism, 9,10 genomic and epigenetic alterations also modulate the metabolism in GBM. 11,12 The analysis of the GBM metabolism is gaining interest to improve diagnostic accuracy and to promote therapeutic effects. 13,14 Molecular spectroscopy and mass spectrometry (MS) are common tools for the investigation of metabolites and metabolic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Other common molecular GBM markers like p53, phosphatase and tensin homolog (PTEN), phosphoinositide 3‐kinase (PI3K), epidermal growth factor receptor (EGFR), and 1p/19q have an ambiguous prognostic importance 7 . While major metabolic changes in tumors include enhanced aerobic glycolysis, so‐called the Warburg effect, and glutamine metabolism, 9,10 genomic and epigenetic alterations also modulate the metabolism in GBM 11,12 . The analysis of the GBM metabolism is gaining interest to improve diagnostic accuracy and to promote therapeutic effects 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Despite these novel pieces of evidence suggesting a role of S1P in tumor metabolic aberrations, further studies are needed to explore this less-studied aspect of S1P signaling. In this context, it is worth mentioning that, among different metabolic deregulations, aberrant lipid metabolism has emerged as crucial, not only as an energy source and in providing substrates for membrane synthesis, but also for its role in cellular signaling in both GBM cells and GSCs [307,308]. Concerning lipid signaling, different studies demonstrated that lysophosphatidic acid (LPA), a major membrane-derived lipid-signaling molecule beside S1P, acts as a key player in GBM [309,310].…”
Section: S1p In the Cancer Microenvironment Promotes Deregulated Enermentioning
confidence: 99%